(untitled) (Global Journal of Human-Social Science, 2017)
The implementation of local content policies among developing resource rich countries has experienced mixed results While some countries have achieved positive outcomes others have not fared very well and therefore the question of why some countries are more successful than others during the implementation of local content policies has not been conclusively addressed Using a two-stage comparative analysis this article studies the factors that account for successful local content outcomes in African and Latin America countries The analysis shows that countries with specific local content frameworks that prioritised the development of their national industries are more likely to achieve positive outcomes in terms of employment creation skills development and the participation of their national industry along the oil and gas value chain The analysis further shows that National Oil Companies and enterprise centres have played a key role for the achievement of positive local content outcomes